NON-PHARMACOLOGIC APPROACHES IN THE TREATMENT OF RHEUMATOID ARTHRITIS - Birol Balaban,; A. Kenan Tan,; Rıdvan Alaca, (Archives of Rheumatology, 2002)
Primary goal of treatment in rheumatoid arthritis (RA) is restraining inflamation of joints and other tissues, reducing pain and preventing disease progression. Although, there is no cure for RA, many treatment modalities have been improved to obtain efficacy mentioned above. In addition to medical treatment, nonpharmacologic measures must be applied at the same time to obtain dynamic and suitable treatment of disease. However, there are different applications according to acute and chronic phase activity of disease. Medical rehabilitation includes regular procedures and helps patients to realize their functional and occupational activities. Fundamental rehabilitation therapy of rheumatoid arthritis comprises treatment approach which prevents functional loss and provides functional adequacy.